Action of two endocrine disrupters on the sexual differenciation of Nile tilapia - Passos Neto, Oscar; Santos, André; Silva, José Roberto; Mota, Francisco Suetônio (Revista Ciência Agronômica, 2019)
Endocrine disruptors are exogenous substances that can impair one or more functions of the endocrine system and cause adverse effects to the health of an intact organism. The main goal of this study was to evaluate the effect of the endocrine disruptors 17β-estradiol (E2) and 17α-ethinyl estradiol (EE2) on the sexual differentiation of Nile tilapia during spawning. Six treatments and one control with three replications, totalizing 21 experimental units, were assessed in a completely randomized design. Hormones were dosed at concentrations of 250, 500, and 1,000 ng L−1 (treatments E2–250, E2–500, E2–1,000, EE2–250, EE2–500, and EE2–1,000). Exposure to hormones occurred during the first 28 days of life. After this period, water was completely renewed and individuals kept in their respective experimental units for another 60 days, totaling 88 days. At the end of this period, animals were euthanized by ice desensitization for gonad extraction, slide preparation, and observation under an optical microscope. At the end of the experiment, the results indicated that the type of hormone and hormone concentration differentially affected the parameters of zootechnical performance. A significant difference (p